Production of doubled haploids in spring wheat varieties and crosses - Sharmeen, Farhana; Rahman, Hamidur; Rahman, L; Rahman, KMM; Arifuzzaman, M (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 49-52